Drama Musical Sepatu Kaca - Melisa Zasna; Yusril ril; Sulaiman man (Besaung : Jurnal Seni Desain dan Budaya, 2021)
Glass Shoes drama musical is an alternative whose made by director for attract the public's attention to watching theatrical performances. Based on facts found in the field, the theater has now lost its audience. Therefore, theater artist must make a new breakthrough in giving understanding to the audience, through the work he created. Musical dramas that carry children's tales are based on the importance of providing educational values to character formation. The combination of music, dance and vocals will provide different sensations and provide entertainment for the audience. Koreo and songs created based on the script will convey a sense that is not conveyed by words. This relates to a musical drama featuring three main objects, namely dialogue, dance and singing. The making of dances and songs is done carefully and intensely so as not to stick to one another. The Glass Shoes drama musical uses mobile settings that can be moved and moved quickly as needed. Penyesuaian video art di setiap adegan dapat memberikan visual yang menarik . perpaduan antara setting mobile dan video art serta unsur lainnya akan mewujudkan multi disiplin ilmu yang sejalan. Adjustment of video art in each scene can provide interesting visuals. a combination of mobile settings and video art and other elements will realize multi-disciplines that are in line. The Glass Shoes drama musical using the method from Bertold Brecht will flavor the storyline during the show. The purpose of using the method of Bertold Brecht is to make the audience aware and give a break so that the audience can immediately digest the content delivered in the show. This method is in line with the desire of the worker who has entertainment concepts in the show.